Atmospheric Nitrogen Emission, Deposition, and Air Quality Impacts in China: an Overview - Liu, Xuejun; Xu, Wen; Duan, Lei; Du, Enzai; Pan, Yuepeng; Lu, Xiankai; Zhang, Lin; Wu, Zhiyong; Wang, Xuemei; Zhang, Ying; Shen, Jianlin; Song, Ling; et al. (Current pollution reports, 2017)
Atmospheric reactive nitrogen (N) has induced large impacts on air pollution and ecosystem health worldwide. Atmospheric reactive N emission and deposition have largely increased in China since 1980 due to rapid agricultural, industrial, and urban development. But scientific gaps still remain in the regional and temporal variability in atmospheric N emissions and deposition. Meanwhile, the environmental impacts of N pollution and deposition are of great concern in China. This paper overviews the status of anthropogenic N emissions and deposition and their linkages to air pollution in China. The major findings include two aspects: (1) anthropogenic reactive N (e.g., NH 3 and NO x ) emissions contribute greatly to secondary inorganic aerosol formation and haze pollution and (2) dry N deposition is comparable in importance to wet N deposition, suggesting that both dry and wet deposition should be quantified simultaneously. Future research challenges on atmospheric N emission and deposition are discussed as well. China needs to (1) reduce the uncertainties of national emission inventory of various N species, especially organic N compounds; (2) establish national networks for atmospheric N concentration and deposition monitoring; and (3) evaluate ecological and environmental impacts of N pollution and deposition in typical ecosystems. Last but not least, N deposition modeling tools should be improved based on localized parameters and further used in future N regulation.